Strategies of balanced growth: how the economy is formed under the influence of environmental challenges - Vintoniak, Alla (Herald of Economics, 2024)
Introduction. The modern world is constantly faced with a number of complex economic and environmental challenges that require a comprehensive and balanced approach to their solution. Combining rapid economic development with environmental protection is becoming an increasingly urgent task for countries and enterprises around the world. Purpose. The purpose of the article is to consider the interaction between modern economic strategies and environmental challenges. It is important to analyze how the economy is formed and adapted under the influence of environmental problems, and how this interaction affects the processes of balanced growth. Research methods. In the process of research and writing the article, we used a number of general scientific and special research methods. Among the latter, we highlight the following: literature review: review of scientific literature and academic research on economic development and its impact on the environment; case studies: study of specific cases of companies or countries that successfully implement balanced development strategies, taking into account environmental challenges; system analysis: the use of systems analysis methods to study the interaction between economic and ecological systems and identify key factors affecting their interaction; modeling and simulation: the use of economic and environmental models to predict the possible consequences of adopting different balanced growth strategies. The results. The article examines how modern strategies of balanced growth are formed under the influence of environmental challenges. Various aspects of this interaction are considered, from the negative impact of the economy on the environment to the opportunities that arise as a result of adopting sustainable and environmentally oriented strategies. Examples of effective «green» innovations that can be successfully implemented in modern economic activity are given. Examples of successful merging of economic and environmental interests in real business were studied and key factors contributing to solving this difficult task were identified. Prospects. Possibilities and further prospects of research in the direction of the raised topic: the impact of technological innovations on balanced development; the role of legal regulation in ensuring sustainable development; socio-economic aspects of sustainable development; international aspect of sustainable development; the impact of global climate change on the economy.